Analisis Perbandingan Metode MOORA dan MOOSRA dalam Seleksi Siswa Unggulan - Desty Rahma Fadilla; Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Educational strategies in the current era really need to be developed so that the advantages that each student has can be made into superior achievements. The selection of superior student selection is very important in the education strategy with the aim of getting superior seeds that will be fostered so that they achieve even more and increase the motivation of each student. At present, most schools carry out the selection of superior students manually by taking the value of each student's report card. Selection with a large number of students sometimes makes it difficult for teachers or the school to choose who has the right to be a superior student. The results of the assessment or consideration of each teacher tend to be subjective. So that there are often misunderstandings in making the final decision in determining who is entitled to be a superior student. Therefore, a decision support system is needed that aims to make it easier to select superior students whose results will be effective. In solving the problem of selecting superior students, the author uses the MOORA method and the MOOSRA method. The results of the study prove that the comparison between the MOORA and MOOSRA methods has the same results, where the MOORA method has the highest yield in alternative 3 with a result of 0.2997 and in alternative 3 MOOSRA method with a result of 13.1548.